Engineering Tribology and Biomedical Materials : selected peer-reviewed full text papers from the 4th PST and 2nd ICETAT - Limmatvapirat, Sontaya; Hwang, Yunn-Lin (Trans Tech Publications, Limited, 2021)
Selected peer-reviewed full text papers from the 4th PST and 2nd ICETAT.
Keywords: Tribology.; Biomedical materials.; elektronické knihy; electronic books